Analysis and Thinking of Urban Transportation Planning against the Backdrop of Multi-planning Integration. Issue 1 (March 2020) - Yin, Yixiao; Guo, Zhong; Tang, Yuanwu
Abstract: In recent years, China has shifted from high-speed growth to high-quality development. At the same time, its urban transportation system is also moving from rapid expansion to intensive and efficient development. Though urban transportation system has entered the stage of relative maturity and stability, some problems are impacting heavily on plan implementation, e.g., poorly-developed planning system, overlapped planning management, theory & practice decoupling and lack of some evaluation steps. In the new situation of multi-planning integration, we propose integrating urban transportation planning into the spatial planning system by focusing on transforming and upgrading transportation planning management, and by streamlining the planning relations, unifying planning system, coordinating planning management, regulating planning compilation and improving implementation mechanism, so that urban transportation planning plays the greater role of strategic orientation in multi-planning system.